Carnosine, Small but Mighty-Prospect of Use as Functional Ingredient for Functional Food Formulation - Ivana Jukić; Nikolina Kolobarić; Ana Stupin; Anita Matić; Nataša Kozina; Zrinka Mihaljević; Martina Mihalj; Petar Šušnjara; Marko Stupin; Željka Breškić Ćurić; Kristina Selthofer-Relatić; Aleksandar Kibel; et al. (MDPI AG, 2021)
Carnosine is a dipeptide synthesized in the body from β-alanine and L-histidine. It is found in high concentrations in the brain, muscle, and gastrointestinal tissues of humans and is present in all vertebrates. Carnosine has a number of beneficial antioxidant properties. For example, carnosine scavenges reactive oxygen species (ROS) as well as alpha-beta unsaturated aldehydes created by peroxidation of fatty acid cell membranes during oxidative stress. Carnosine can oppose glycation, and it can chelate divalent metal ions. Carnosine alleviates diabetic nephropathy by protecting podocyte and mesangial cells, and can slow down aging. Its component, the amino acid beta-alanine, is particularly interesting as a dietary supplement for athletes because it increases muscle carnosine, and improves effectiveness of exercise and stimulation and contraction in muscles. Carnosine is widely used among athletes in the form of supplements, but rarely in the population of cardiovascular or diabetic patients. Much less is known, if any, about its potential use in enriched food. In the present review, we aimed to provide recent knowledge on carnosine properties and distribution, its metabolism (synthesis and degradation), and analytical methods for carnosine determination, since one of the difficulties is the measurement of carnosine concentration in human samples. Furthermore, the potential mechanisms of carnosine's biological effects in musculature, metabolism and on immunomodulation are discussed. Finally, this review provides a section on carnosine supplementation in the form of functional food and potential health benefits and up to the present, neglected clinical use of carnosine.